1986
DOI: 10.1089/dna.1986.5.333
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Biotinylating Oligonucleotide Probes for Use in Molecular Hybridizations

Abstract: A new method is described for biotinylation of oligonucleotide probes for use in molecular hybridization reactions. Biotin-11-dUTP residues were added enzymatically, using terminal deoxynucleotidyl transferase, to the 3' terminus of a synthetic oligonucleotide prepared from the known nucleotide sequence for adenosine deaminase. The biotinylated probe was hybridized to DNA and mRNA selectively immobilized on nitrocellulose and detected by sequential incubation of the nitrocellulose membrane with avidin and biot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…After exposure to a UV light source, cells are harvested and then lysed using the method of Hirt (11), which allows for the extraction of small DNA fragments away from most of the high molecular weight genomic DNA in the cell. After extensive treatment with RNase and protease to remove RNA and proteins, respectively, the DNAs are 3′-end labeled with terminal transferase and the nucleotide analog biotin-11-dUTP (or biotin-11-UTP) (12). The biotinylated DNAs are then separated by denaturing urea-PAGE and transferred onto a nylon membrane.…”
Section: Resultsmentioning
confidence: 99%
“…After exposure to a UV light source, cells are harvested and then lysed using the method of Hirt (11), which allows for the extraction of small DNA fragments away from most of the high molecular weight genomic DNA in the cell. After extensive treatment with RNase and protease to remove RNA and proteins, respectively, the DNAs are 3′-end labeled with terminal transferase and the nucleotide analog biotin-11-dUTP (or biotin-11-UTP) (12). The biotinylated DNAs are then separated by denaturing urea-PAGE and transferred onto a nylon membrane.…”
Section: Resultsmentioning
confidence: 99%
“…However, we found that other cell lysis buffers containing non-ionic or ionic detergents can also be used for this approach, indicating that the excised oligomer products of excision repair are highly soluble and readily extractable from cells. For the non-radioisotopic DNA labeling, we use terminal transferase and the nucleotide analog biotin-11-dUTP to label the 3′-end of the excised oligonucleotides (36). The labeled DNAs are then subjected to denaturing urea-polyacrylamide gel electrophoresis and transfer to a nylon membrane.…”
Section: Development Of a Non-radioisotopic In Vivo Excision Assaymentioning
confidence: 99%
“…Specificity is achieved by targeting conserved or unique rRNA sequences. In most cases the probes are labelled with biotin to react with avidin, which is coated on a plate (Riley, Marshall, & Coleman, 1986). For pathogens and beer spoiling organisms, 16S rRNA, 23S rRNA or respectively the corresponding DNA are usually selected as the target (Almeida et al, 2010;Frischer, Floriani, & Nierzwicki-Bauer, 1996;Fuchs, Syutsubo, Ludwig, & Amann, 2001).…”
Section: Probesmentioning
confidence: 99%